Diversity and Community Structure of Arthropods on Rice Ecosystem - J. Jauharlina; H. Hasnah; M. Ikram Taufik (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Arthropods biodiversity on a rice ecosystem plays an important role related to the pest management. This research aimed to investigate the diversity and community structure of arthropods in the rice ecosystem. It was conducted in Lembah Seulawah, Aceh Besar Regency, Indonesia from February to August 2016. Sweep net was used to collect insects on four rice plots at 35, 45 and 55 days after transplanting (DAT) as vegetative, transition and generative stages respectively. Result showed that the twenty-five morpho-species found at vegetative stage and it was the highest. They were categorized as phytophagous insects, spiders, predatory insects, parasitoid, and neutral insects. Each arthropod’s category was in the higher abundance at vegetative stage, except for phytophagous arthropod. The Shannon-Wiener diversity index (H') was significantly higher at vegetative stage than the remaining stages, while Simpson Dominance index (C) and Species Evenness (E) indices were not significantly different among the three observed stages.